Verificación del cumplimiento de la Norma AWS D1.1 en la construcción y montaje de estructuras metálicas de altura en el Norte de Guayaquil - Cañizares Villagrán, Mariano Vicente (2023)
The objective of this research is to develop a form for the visual inspection that will be carried out on ten works with a metallic structure in the construction process in the north of Guayaquil. This inspection makes it possible to evaluate and document compliance with the AWS D1.1 standard, which in section two determines all the mandatory requirements of the regulation, section five lists the requirements for the welding process, while section six describes the required tests. This information makes it possible to propose 30 very important visual inspection points to verify whether or not the regulations are followed in the city. Visual inspection is a process that must be carried out constantly, for metal structures, much more if they are exposed and do not have the respective maintenance. In this way we can provide a technical criterion that allows prolonging the useful life of the structure.